2018
DOI: 10.1190/geo2016-0663.1
|View full text |Cite
|
Sign up to set email alerts
|

Application of optimal transport and the quadratic Wasserstein metric to full-waveform inversion

Abstract: Conventional full-waveform inversion (FWI) using the least-squares norm (L 2 ) as a misfit function is known to suffer from cycle skipping. This increases the risk of computing a local rather than the global minimum of the misfit. In our previous work, we proposed the quadratic Wasserstein metric (W 2 ) as a new misfit function for FWI. The W 2 metric has been proved to have many ideal properties with regards to convexity and insensitivity to noise. When the observed and predicted seismic data are regarded as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
199
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 229 publications
(202 citation statements)
references
References 34 publications
3
199
0
Order By: Relevance
“…In Figure 8, we show a true wave speed model that we used to generate synthetic data, an initial guess as well as the inversion results obtained with the L 2 metric and the W 2 metric. The computational details of this numerical experiment can be found in [35]. Here we are mainly interested in demonstrating the smoothing effect of the quadratic Wasserstein metric at the initial guess that is far from the true wave speed field.…”
Section: Wasserstein Data Matching In Seismic Imagingmentioning
confidence: 99%
“…In Figure 8, we show a true wave speed model that we used to generate synthetic data, an initial guess as well as the inversion results obtained with the L 2 metric and the W 2 metric. The computational details of this numerical experiment can be found in [35]. Here we are mainly interested in demonstrating the smoothing effect of the quadratic Wasserstein metric at the initial guess that is far from the true wave speed field.…”
Section: Wasserstein Data Matching In Seismic Imagingmentioning
confidence: 99%
“…For actual seismic data processing, if the length of a seismogram is T 0 , the exact expression of the quadratic Wasserstein distance in one dimension is as follows (Yang et al, ): W2()f,g=0T0tG1Fnormalt2f()tnormaldt. …”
Section: Quadratic‐wasserstein‐metric‐bsed Seismic Adjoint Tomographymentioning
confidence: 99%
“…If the misfit between the synthetic and observed data is examined from another point of view, a mapping can be considered to exist between them (Ma & Hale, ; Engquist & Froese, ; Métivier et al, ; Yang et al, ). Recently, a novel measure of misfit related to optimal transport was proposed by Engquist and Froese ().…”
Section: Introductionmentioning
confidence: 99%
“…Our work is motivated in part by [7,8,34], where the authors use the quadratic Wasserstein metric to solve Full-Waveform Inversion (FWI) problems. In particular, it is demonstrated that the quadratic Wasserstein metric, as opposed to the L 2 norm, provides an effective measure of the misfit between given data and computed solution.…”
Section: Prior Workmentioning
confidence: 99%
“…Our work extends that of [7,8,34] by considering different inverse problems, a more general noise model, and we use a different Wasserstein metric. See section 4.4 for more detail.…”
Section: Our Contributionmentioning
confidence: 99%